Robustness metrics for optical networks - Noor Aishah Zainiar; Farabi Iqbal; ASM Supa’at; Adam Wong Yoon Khang (Institute of Advanced Engineering and Science, 2020)
Telecommunication networks are vulnerable towards single or simultaneous nodes/links failures, which may lead to the disruption of network areas. The failures may cause performance degradation, reduced quality of services, reduced nodes/links survivability, stability, and reliability. Therefore, it is important to measure and enhance the network robustness, via the use of robustness metrics. This paper gives an overview of several robustness metrics that are commonly used for optical networks, from the structural, centrality and functional perspectives.